Anterior Spinal Artery Syndrome Complicating Massive Paravertebral Abscess - Uchida, Kenzo; Kobayashi, Shigeru; Nakajima, Hideaki; Yayama, Takafumi; Bangirana, Alexander; Baba, Hisatoshi (Journal of Orthopaedic Science, 2008)
Anterior spinal artery (ASA) syndrome is associated with a variety of conditions, such as aortic dissection or traumatic rupture, complications of aortic surgery, thrombosis or embolism, hematomyelia, vasculitis, ver tebrocervical arthrosis, or coagulopathy,1–5 although the condition could be also idiopathic. The clinical features include sudden onset of significant intractable back pain followed by rapid development of paraparesis, dissociated sensory loss, and bladder and bowel disturbances.We describe here a case of ASA syndrome associated with paravertebral abscess and pyothorax in a patient known to have malignant rheumatoid arthritis and renal failure. We discuss the possible mechanism of ASA syndrome in this unusual case with review of the literature